A Composite of Cubic Calcium-Magnesium Sulfate and Bioglass for Bone Repair - Chen, Yan; Zhang, Tie; Zhang, Qi; Lei, QingJian; Gao, ShiJie; Xiao, KangWen; Yan, FeiFei; Cai, Lin (Frontiers in Bioengineering and Biotechnology, 2022)
Calcium sulfate(CS) bone cement has been shown to have good biocompatibility and can be used as a bone filler for repairing bone defects. However, its clinical application is limited due to the low compressive strength and weak bone repair activity. To this end, in this study, cubic crystalline magnesium-doped calcium sulfate (MgCS) was prepared and mixed with bioglass(BG) to form a composite bone cement (MgCS/BG). The results show that the cubic crystal calcium sulfate helps to increase the compressive strength of the composite bone cement to more than 60 MPa. More importantly, the obtained magnesium-doped composite bone cement can promote the adhesion and differentiation of mesenchymal stem cells, and has good bioactivity. Through the skull defect model, it was found that MgCS/BG can significantly enhance bone defect repair and new bone formation. This new composite MgCS/BG has very good clinical application and transformation prospect.